Draft Annual Plan 1970-71 Government of Manipur - Planning Commission (Planning Commission, 1970)
Agriculture is the main-stay of the people of Manipur. Out of the total geographical area of about 49.04 lakh acres, 5.56 lakh acres are estimated to be under cultivation every year. The main crops are paddy, maize, potato, pulse, etc. Paddy is grown mainly in the valley areas which comprises about 8% of the total geographical areas. Manipur which was originally self-sufficient in food grains has turned marginally deficient in the matter in the recent years. The Fourth Five Year Plan of the Territory envisages a goal of self-sufficiency in respect of food grains.
Government of Manipur